Biochemical and immunocytochemical characterization of coronins in platelets. (2nd October 2020) - Riley, David R. J.; Khalil, Jawad S.; Naseem, Khalid M.; Rivero, Francisco
Abstract: Rapid reorganization of the actin cytoskeleton in response to receptor-mediated signaling cascades allows platelets to transition from a discoid shape to a flat spread shape upon adhesion to damaged vessel walls. Coronins are conserved regulators of the actin cytoskeleton turnover but they also participate in signaling events. To gain a better picture of their functions in platelets we have undertaken a biochemical and immunocytochemical investigation with a focus on Coro1. We found that class I coronins Coro1, 2 and 3 are abundant in human and mouse platelets whereas little Coro7 can be detected. Coro1 is mainly cytosolic, but a significant amount associates with membranes in an actin-independent manner and does not translocate from or to the membrane fraction upon exposure to thrombin, collagen or prostacyclin. Coro1 rapidly translocates to the Triton insoluble cytoskeleton upon platelet stimulation with thrombin or collagen. Coro1, 2 and 3 show a diffuse cytoplasmic localization with discontinuous accumulation at the cell cortex and actin nodules of human platelets, where all three coronins colocalize. Our data are consistent with a role of coronins as integrators of extracellular signals with actin remodeling and suggests a high extent of functional overlap among class I coronins in platelets.